CO2 exposure drives a rapid pH response in live adult Drosophila. - Zimmerman, S.G.; Berg, C.A. (PLoS ONE, 2024)
CO2 anesthesia is the most common method for immobilizing Drosophila for research purposes. But CO2 exposure has consequences-it can impact fertility, behavior, morphogenesis, and cytoskeletal dynamics. In this respect, Drosophila is an outstanding model for studying the impact of CO2 exposure on tissues. In this study we explored the response of intracellular pH (pHi) to a one-minute CO2 pulse using a genetically encoded, ubiquitously expressed pH sensor, tpHusion, to monitor pHi within a live, intact, whole fly. We compared wild-type flies to flies lacking Imaginal disc growth factors (Idgfs), which are chitinase-like proteins that facilitate developmental processes and the innate immune response. Morphogenetic and cytoskeletal defects in Idgf-null flies are enhanced after CO2 exposure. We found that pHi drops sharply within seconds of the beginning of a CO2 pulse and recovers over several minutes. The initial profile was nearly identical in control and Idgf-null flies but diverged as the pHi returned to normal. This study demonstrates the feasibility of monitoring pH in live adult Drosophila. Studies exploring pH homeostasis are important for understanding human pathologies associated with pH dysregulation.